DFT analysis and bioactivity of 2-((E)-(4-methoxybenzylimino)methyl)phenol and its Ni(II) and Pd(II) complexes - Amalina Mohd Tajuddin; El Hassane Anouar; Kalavathy Ramasamy; Bohari M. Yamin; Abdulrahman I. Alharthi; Hadariah Bahron (Arabian Journal of Chemistry, 2017)
This paper reports the synthesis, characterisation and DFT analysis of an N,O bidentate Schiff base, ((E)-(4-methoxybenzylimino)methyl)phenol, (L1c) and its Ni(II) and Pd(II) complexes. The structures were elucidated via elemental analysis, UV–Visible, NMR, IR and single crystal X-ray diffraction. Complexation of L1c with Ni(II) and Pd(II) was observed to induce different degrees of bathochromic effect on n → π∗ and π → π∗ electronic transitions. A comparison of the experimental data of UV–Visible, NMR, IR and X-ray with those calculated using DFT and TD-DFT methods where five hybrid functionals were tested in gas, IEF-PCM and SS-PCM models was also carried out. The results show that the reproduction of maximum absorption bands n → π∗ and π → π∗ is strongly related to the tested hybrid functionals and solvatochromic effects. Relatively good concordance was obtained between experimental and calculated NMR chemical shifts, IR and X-ray parameters. A bioactivity evaluation against HCT116 and Escherichia coli displayed that the parent ligand L1c is a more superior anticancer and antibacterial agent than the positive controls of 5FU and gentamicin respectively. However, both complexes showed poor activity as anticancer agent and no activity observed against tested bacteria.